Adolescent activity vs passivity on social networking websites and its relations with loneliness and personality traits - Pociūtė, Birutė; Krancaitė, Erika (Psichologija, 2012)
With the growing popularity of Internet communication among adolescents, the Internet has become an important social context of their development. Recent data have revealed that there are already are over 1 million Facebook users in Lithuania; one-fifth of Facebook users consists of adolescents 13–17 years old. Investigators have assumed that one of the main reasons encouraging individuals to use social network websites is to facilitate psychosocial problems such as loneliness. Scientists are discussing the Internet possibilities to extend the limits of real communication or to take its place. The aim of this investigation was to reveal the features of adolescents’ use of the social networking website Facebook and its relations with loneliness and personality traits. The study included 175 adolescents, age 13 to 18 years (M = 15.4; SD = 1.102). They filled in a questionnaire on the use of social website Facebook, UCLA loneliness scale (version 3; Russell, 1996), the personality traits questionnaire NEO-FFI (Costa and McCrae, 1992). The results show that 81.1% of teens are users of the social network site Facebook and spend very much time on Facebook, publishing a lot of personal information in the web profiles without paying due attention to privacy preservation. On the website, adolescents accumulate large amounts of “friends”, although relationship transfer from the reality to the Internet prevails. The study revealed two main activity types: socially proactive and socially passive. The results also show that the personality traits have an impact on teenagers’ behaviour on Facebook: neurotic teenagers’ activity on Facebook is socially passive; extraverted adolescents support the social enhance attitude, but they are not enough to communicate online and tend to actually meet people that first were met on Facebook. Teenagers with a highly expressed consciousness, in general, are not active Facebook users, and do not try to compensate for their loneliness by using the social network website Facebook. Very lonely teenagers show a socially passive activity, or a passive activity dominates, or in combination with a social activity. At the time, loneliness decreases, depending on how much time per day adolescents use the Facebook website.
Keywords: Social Network Site Facebook; personality traits; loneliness; activity on social Network Site